2002
DOI: 10.1067/mpd.2002.126301
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cardiac abnormalities in children with human immunodeficiency virus infection: The prospective P2 C2 HIV study

Abstract: Objective-To describe the 5-year cumulative incidence of cardiac dysfunction in human immunodeficiency virus (HIV)-infected children.Study design-We used a prospective cohort design, enrolling children at 10 hospitals. Group I included 205 vertically HIV-infected children enrolled at a median age of 1.9 years. Group II consisted of 600 HIV-exposed children enrolled prenatally or as neonates, of whom 93 were ultimately HIV-infected. The main outcome measures were echocardiographic indexes of left ventricular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 25 publications
4
28
1
3
Order By: Relevance
“…The relative risk for death during the 5-year follow-up period is 8.5 to 14.6 times higher than in children without these complications [7]. Results from the P 2 C 2 HIV study show increasingly abnormal LV structure and function in the first 3 years of life, resulting in persistent mild LV dysfunction and increased LV mass.…”
Section: Cardiac Involvement In Pediatric Hiv Infectionmentioning
confidence: 82%
“…The relative risk for death during the 5-year follow-up period is 8.5 to 14.6 times higher than in children without these complications [7]. Results from the P 2 C 2 HIV study show increasingly abnormal LV structure and function in the first 3 years of life, resulting in persistent mild LV dysfunction and increased LV mass.…”
Section: Cardiac Involvement In Pediatric Hiv Infectionmentioning
confidence: 82%
“…For female donors overall, the older age subgroups had significantly higher HTLV-1 seroprevalence compared with younger subgroups in all pair-wise comparisons (p < 0.0001) except between G [16][17][18][19] and G [20][21][22][23][24][25][26][27][28][29] (Table 1). This trend was also observed for male donors, where G [16][17][18][19] and G 20-29 were not significantly different and all other pair-wise comparisons showed significantly higher seroprevalence for older subgroups (p = 0.0087 between G 20-29 and G 30-39 , and p < 0.0001 for all other pair-wise comparisons, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, a study conducted on ∼1800 infants born to HCV-infected mothers demonstrated twice as much vertical transmission to females as males. 23 For HIV, intra-uterine infection is reported to be female dominant, [24][25][26][27][28] whereas post-natal infection is more common for males. 29,30 One might speculate that the gender-specific risk of transmission varies according to the transmission route.…”
Section: Potential Mechanism Of Paradoxical Male Predominance Of Htlvmentioning
confidence: 99%
“…The applicability of data previously published about the cardiac involvement in patients using protease inhibitors is unknown, and it is necessary to verify if this new therapy has modified the incidence of cardiac manifestations 10 . This current study aims to describe the cardiac clinical manifestations, results of laboratory tests that evaluate the immunological status and echocardiographic findings after 18±6 months of AIDS diagnosis, trying to relate them to the type of antiretroviral therapy available.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of dysfunction was quantified by Δ% LV, that is, the lower the percentage, the more severe the left ventricular involvement. Values of 28% to 25% were considered mild dysfunction and, in most cases, patients were asymptomatic; values <25% and up to 19% were considered as moderate dysfunction, usually with clinical symptoms, and values lower than 19% were considered as severe dysfunction, almost always associated with a clinical picture of more severe heart failure 10 .…”
Section: Introductionmentioning
confidence: 99%